TARI JELAH ESENSI GERAK BARIS CINA DALAM BENTUK KONTEMPORER - I Gede Coki Indrajaya; I Gede Oka Surya Negara; Ni Komang Sri Wahyuni (Jurnal IGEL : Journal Of Dance, 2023)
Through the Independent Learning–Independent Campus policy, which was implemented by the Minister of Education and Culture (Mendikbud), students chose to work with Geoks partners in Singapadu Village, Gianyar Regency. In this paper, the focus is on the Independent Study learning method where this writing leads to the activities of students who have a passion for realizing great works that will be displayed, and of course works that come from innovative ideas. The Renon tradition has a sacred dance, namely the Chinese Baris Dance. This sacred dance is also an intangible world cultural heritage. This Chinese Baris Dance consists of two groups of dancers, one group wearing black clothes, one group wearing white clothes, which symbolizes the battles of the I Renggan and I Renggin groups with different beliefs (good and evil). Each of these groups consists of 9 dancers where each group has a leader who is often referred to as a pengater. The process of creating this dance work, using the method of Hawkins (2003) in his book entitled Creating through the Dance, reveals the process of creating a dance in 3 stages, namely: Exploration, improvisation and Forming. This JELAH dance is a contemporary dance that depicts the symbol of the readiness of soldiers who want to fight in war.   Keywords: chinese line dance, spiritual, contemporary